Formulation, optimization, and evaluation of self-emulsifying drug delivery systems of nevirapine - Chintalapudi, Ramprasad (Int J Pharm Investig, 2015)
BACKGROUND: The aim of the present study was to formulate and optimize the self-emulsifying drug delivery systems (SEDDS) of nevirapine (NVP) by use of 2(2) factorial designs to enhance the oral absorption of NVP by improving its solubility, dissolution rate, and diffusion profile. SEDDS are the isotropic mixtures of oil, surfactant, co-surfactant and drug that form oil in water microemulsion when introduced into the aqueous phase under gentle agitation. MATERIALS AND METHODS: Solubility of NVP in different oils, surfactants, and co-surfactants was determined for the screening of excipients. Pseudo-ternary phase diagrams were constructed by the aqueous titration method, and formulations were developed based on the optimum excipient combinations with the help of data obtained through the maximum micro emulsion region containing combinations of oil, surfactant, and co-surfactant. The formulations of SEDDS were optimized by 2(2) factorial designs. RESULTS: The optimum formulation of SEDDS contains 32.5% oleic acid, 44.16% tween 20, and 11.9% polyethylene glycol 600 as oil, surfactant, and co-surfactant respectively. The SEDDS was evaluated for the following drug content, self-emulsification time, rheological properties, zeta potential, in vitro diffusion studies, thermodynamic stability studies, and in vitro dissolution studies. An increase in dissolution was achieved by SEDDS compared to pure form of NVP. CONCLUSION: Overall, this study suggests that the dissolution and oral bioavailability of NVP could be improved by SEDDS technology.